2005
DOI: 10.1038/nrm1593
|View full text |Cite
|
Sign up to set email alerts
|

Organization of vesicular trafficking in epithelia

Abstract: Experiments using mammalian epithelial cell lines have elucidated biosynthetic and recycling pathways for apical and basolateral plasma-membrane proteins, and have identified components that guide apical and basolateral proteins along these pathways. These components include apical and basolateral sorting signals, adaptors for basolateral signals, and docking and fusion proteins for vesicular trafficking. Recent live-cell-imaging studies provide a real-time view of sorting processes in epithelial cells, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
575
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(591 citation statements)
references
References 159 publications
13
575
2
1
Order By: Relevance
“…Apical and basolateral PM proteins are synthesized at the endoplasmic reticulum, transported to the Golgi complex and sorted at the trans golgi network (TGN) into distinct apical and basolateral vesicular routes (Simons and Wandinger-Ness, 1990;Rodriguez-Boulan and Powell, 1992). After arrival at the cell surface, apical and basolateral membrane proteins are internalized into separate apical sorting endosomes and basal sorting endosomes (Figure 2), (Breitfeld et al, 1989;Mostov et al, 2003;Rodriguez-Boulan et al, 2005), mixed in common recycling endosomes and sorted into distinct recycling routes back to their original PM domain. The apical recycling route includes the apical recycling endosome (Apodaca et al, 1994;Brown et al, 2000).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…Apical and basolateral PM proteins are synthesized at the endoplasmic reticulum, transported to the Golgi complex and sorted at the trans golgi network (TGN) into distinct apical and basolateral vesicular routes (Simons and Wandinger-Ness, 1990;Rodriguez-Boulan and Powell, 1992). After arrival at the cell surface, apical and basolateral membrane proteins are internalized into separate apical sorting endosomes and basal sorting endosomes (Figure 2), (Breitfeld et al, 1989;Mostov et al, 2003;Rodriguez-Boulan et al, 2005), mixed in common recycling endosomes and sorted into distinct recycling routes back to their original PM domain. The apical recycling route includes the apical recycling endosome (Apodaca et al, 1994;Brown et al, 2000).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…Basolateral sorting is guided by basolateral sorting signals (Keller and Simons, 1997;Rodriguez-Boulan et al, 2005), and they include: short tyrosine motifs such as Yxxf or NPXY (Brewer and Roth, 1991;Le Bivic et al, 1991;Matter et al, 1992), dileucine (Hunziker and Fumey, 1994) or monoleucine motifs with nearby acidic patches (Deora et al, 2004), PxxP, found in EGFR and pleomorphic motifs that do not yet fall into established classes, found in NCAM (Le Gall et al, 1994), transferrin receptor (Odorizzi and Trowbridge, 1997) and polymeric IgA receptor (Aroeti and Mostov, 1994) ( Figure 2). Yeast 2 and 3 hybrid assays (Ohno et al, 1995;Janvier et al, 2003) demonstrated that Yxxf motifs interact with the m subunit of AP adaptors (AP1, AP2, AP3, AP4), whereas dileucine motifs of the type [DE]XXXL [LI] bind to g and s1 subunits of AP1 and to d and s3 subunits of AP3 (Kirchhausen, 2000;Bonifacino and Traub, 2003).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…This is 171 based on highly specific sorting machinery at the exit of the 172 TGN (Rodriguez-Boulan et al 2005). Cytoskeleton ele-173 ments form part of this machinery, and the integrity of 174 actin filaments is necessary for efficient delivery of some 175 proteins destined for the apical or the basolateral plasma 176 membrane domains in both polarized and non-polarized 177 cells, but not for the transport of lipid raft-associated pro-178 teins (Jacob et al 2003;Lazaro-Dieguez et al 2007;179 Lebreton et al 2008) (Fig.…”
mentioning
confidence: 99%
“…During embryonic and postnatal development, these transport events are tightly coordinated with the activities of other cellular systems (e.g., the cytoskeleton, adhesion patches) through numerous signaling proteins (Nelson, 2003;Rodriguez-Boulan et al, 2005). Mutations in these regulatory proteins can therefore induce genetic disorders that are frequently accompanied by severe phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane transport has a fundamental role in tissue biogenesis through its supply of extracellular matrix components, surface adhesion molecules, and the lipids and proteins that are essential for specific cell-surface domains (Mostov et al, 2003;Nelson, 2003;Rodriguez-Boulan et al, 2005). During embryonic and postnatal development, these transport events are tightly coordinated with the activities of other cellular systems (e.g., the cytoskeleton, adhesion patches) through numerous signaling proteins (Nelson, 2003;Rodriguez-Boulan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%